1994
DOI: 10.1093/jn/124.5.615
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sphingomyelin Inhibits 1,2-Dimethylhydrazine–Induced Colon Cancer in CF1 Mice

Abstract: Sphingolipids are in all eukaryotic cells and modulate cell growth, differentiation, and transformation; however, little is known about the physiological effects of their consumption. Mice were fed diets supplemented with milk sphingomyelin to determine effects on colon carcinogenesis. Cancer was initiated in CF1 mice by 1,2-dimethylhydrazine. Mice were then fed AIN76A diets supplemented with 0.025 to 0.1 g sphingomyelin/100 g for 28 wk until the supply of sphingomyelin was depleted and then fed unsupplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(161 citation statements)
references
References 21 publications
5
156
0
Order By: Relevance
“…It has been shown that supplement of SM in the diet to normal mice significantly reduced the number of aberrant crypt foci in the colon and inhibited the development of colon carcinoma induced by chemical carcinogens (Dillehay et al, 1994;Schmelz et al, 1996). In agreement with this, human colonic carcinomas as well as colonic mucosa of rats treated with chemical dimethylhydrazine, show an accumulation of SM (Dudeja et al, 1986;Merchant et al, 1995), which may well be the result of a reduced SMase activity as shown in our previous work (Hertervig et al, 1997).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that supplement of SM in the diet to normal mice significantly reduced the number of aberrant crypt foci in the colon and inhibited the development of colon carcinoma induced by chemical carcinogens (Dillehay et al, 1994;Schmelz et al, 1996). In agreement with this, human colonic carcinomas as well as colonic mucosa of rats treated with chemical dimethylhydrazine, show an accumulation of SM (Dudeja et al, 1986;Merchant et al, 1995), which may well be the result of a reduced SMase activity as shown in our previous work (Hertervig et al, 1997).…”
Section: mentioning
confidence: 99%
“…Human colonic carcinomas, as well as the colonic mucosa of rats treated with colonic carcinogens, are associated with an accumulation of SM (Dudeja et al, 1986;Merchant et al, 1995). In normal mice, dietary supplement of SM has been shown to reduce the number of aberrant colonic crypt foci (considered to be early biomarkers of dysplastic change in the epithelium) and mice given 1,2-dimethyl-hydrazine, a colonic carcinogen, together with SM, showed an increase in the proportion of adenomas versus adenocarcinomas, indicating a possible chemopreventive role (Dillehay et al, 1994;Schmelz et al, 1996). We recently found that human colorectal carcinomas had a 75% reduction of alkaline SMase activity compared to the normal adjacent mucosa (Hertervig et al, 1997).…”
mentioning
confidence: 99%
“…Some studies have demonstrated the anticarcinogenic potential of phospholipids, especially against colon cancer (Dillehay et al, 1994;Schmelz et al, 1996Schmelz et al, , 1998, as well as their protective effect against bacterial toxins and infection (Rueda et al, 1998;Sprong et al, 2002). The antimicrobial activity of RT 3 and RT 4 prepared by blending dahi with fermented paneer whey in 40 and 30 per cent, respectively had significant higher antimicrobial activity against selected pathogens compared to the control RT 5 (containing 70 per cent dahi with 30 per cent water).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Sphingolipids and metabolites Reduction of the number of aberrant crypt foci and adenocarcinomas Dillehay et al [1994] Shift in tumor type (malignant → benign) Schmelz et al [1996; Symolon et al [2004]; Spitsberg [2005] Anticholesterolemic Noh & Koo [2003; Nyberg et al [2000]; Eckhardt et al [2002] Protection of the liver from fat-and cholesterolinduced steatosis Duivenvoorden et al 2006 Suppression of gastrointestinal pathogens Sprong et al [2002]; Vesper et al [1999]; Pfeuffer & Schrezenmeir [2001] Neonatal gut maturation Oshida et al [2003] Myelination of the developing central nervous system Oshida et al [2003] Endogenous modulators of vascular function Michel et al [2007] Associated with age-related diseases and the development of Alzheimer Parodi [2001]; Spitsberg [2005] Sphingosine 1-phosphate Mitogenic Zhang et al [1990Zhang et al [ , 1991 Phosphatidyl-serine (PS) Restore normal memory on a variety of tasks McDaniel et al [2003] Positive effects on alzheimer patients Crook et al [1992]; Heiss et al [1994]; Pepeu et al [1996]; Gindin et al [1998]; Hashioka et al [2004] Improve exercise capacity of exercising humans Kingsley [2006] Phosphatidylcholine (PC) Support liver recovery from toxic chemical attack or viral damage Kidd [2002] Protects the human GI mucosa against toxic attack Anand et al [1999] Reduction of necrotising enterocolitis Carlson et al [1998] Lysophosphat-idylcholine (lyso PC) Bacteriostatic and bactericidal capacity van Rensburg et al [1992] Strong gastroprotective role in the duodenal mucosa ; ; Kivinen et al [1995] Other components Vitamin E and carotenoids Antioxidants Spitsberg [2005] as a mediator of senescence in a cell culture...…”
Section: Polar Lipidsmentioning
confidence: 99%